Diversity of Lactic Acid Bacteria in Senduro Goat Milk - Trimulyono, Guntur; Salamun, Salamun; Fatimah, Fatimah (Universitas Negeri Surabaya, 2025)
Goat milk is currently widely consumed by Indonesian people. The Senduro breed of goats is one of the milk-producing goats widely cultivated by farmers in Senduro District, Lumajang Regency, East Java. Based on several studies, goat milk is a habitat for lactic acid bacteria, and research has been conducted on isolating lactic acid bacteria from goat milk. This study aims to isolate lactic acid bacteria from Senduro goat milk samples characterized morphologically and biochemically. The pour plate method was used to isolate lactic acid bacteria, followed by the purification of isolates using the streak plate method. Colony characterization was carried out by observing the colonies' shape, edge, elevation, surface, and color. Gram staining, endospore staining, catalase test, and motility test were carried out to confirm lactic acid bacteria isolates. This study has successfully isolated 50 isolates of lactic acid bacteria that have Gram-positive, non-endospore, catalase-negative, and non-motile characteristics. The morphological characteristics of lactic acid bacteria isolate colonies from milk samples from the three farms showed diversity. Several isolates from the three farms showed similar characteristics. Further potential testing and identification of each lactic acid bacteria isolate is necessary to provide information regarding its roles.